A Novel Lens orientalis Resistance Source to the Recently Evolved Highly Aggressive Australian Ascochyta lentis Isolates - Dadu, Rama H. R.; Ford, Rebecca; Sambasivam, Prabhakaran; Gupta, Dorin (Frontiers in Plant Science, 2017)
Substantial yield losses and poor seed quality are frequently associated with Ascochyta blight infection of lentil caused by Ascochyta lentis. Recently reported changes in aggressiveness of A. lentis have led to decreased resistance within cultivars such as Northfield and Nipper in Australia. Furthermore, the narrow genetic base of the current breeding program remains a risk for further selective pathogen evolution to overcome other currently used resistances. Therefore, incorporation of potentially novel and diverse resistance genes into the advanced lines will aid to improve cultivar stability. To identify these, 30 genotypes sourced from five wild species (Lens orientalis, L. odomensis, L. ervoides, L. nigricans and L. lamottei), including eight previously reported resistance sources, were screened for disease reaction to two recently isolated and highly aggressive isolates. Subsequently, two L. orientalis accessions were found highly resistant and a further six L. nigricans, one L. odemensis, one L. ervoides, one L. lamottei and one L. orientalis accessions were moderately resistant. Several of these were more resistant than the currently deployed resistance source, ILL 7537. Furthermore, L. orientalis accession ILWL 180 was consistently resistant against other highly aggressive isolates recovered from diverse geographical lentil growing regions and host genotypes, suggesting stability and potential for future use of this accession in the Australian lentil breeding program.